A Footprint Study of Educational Modernization in Islamic Elementary Schoo - Gunawan, Gunawan; Adyan, Muhammad; Marisa, Siti (Jurnal Basicedu, 2023)
Modernization is a necessity in madrasas, Islamic boarding schools, and Islamic educational institutions. This is in accordance with Islamic guidance that other than Allah is new according to human nature which wants change. This study aims to describe the footprints of the process of modernization of education at Al-Azhar Asy-Syarif Islamic Elementary School, North Sumatra. The researcher uses a qualitative methodology with a constructivist approach, this approach assumes that social reality is built and constructed by the individuals involved in it. This approach is taken to reveal how individuals understand and interpret the social reality that occurs around the object of research, with data collection techniques commonly used in the constructivist approach. The results of this study found that the phenomenon of modernization of Islamic schools is a change that occurs in the teaching system in schools, as has been implemented by SD Islam Al Azhar Asy-Syarif, North Sumatra. This can be seen from (1) the adoption of digital-based modern teaching methods; (2) provision of learning facilities that are relevant to the technological era, such as laboratories, digital libraries, and comfortable study rooms; (3) preparation of a learning curriculum that prioritizes improving skills (soft skills), strengthening intellectual insights, and teaching materials that train students' critical thinking and higher-order thinking skills.